CIRCULAR ECONOMY AND LOGISTICS: ENHANCING SUSTAINABLE CONSUMPTION AND PRODUCTION (SDG 12) IN UZBEKISTAN - Samariddin Makhmudov; Shoh-Jаkhon Khаmdаmov; Doniyar Karshiev (International Journal of Artificial Intelligence for Digital Marketing, 2024)
This paper explores the concept of a circular economy and its implications for the logistics sector in Uzbekistan, focusing on Sustainable Development Goal (SDG) 12, which promotes responsible consumption and production. It examines how adopting circular economy principles in logistics can enhance sustainability, reduce waste, and optimize resource use. The paper discusses the current state of logistics and waste management in Uzbekistan, identifies challenges to implementing a circular economy, and proposes strategies for integrating circular practices into the logistics sector. By adopting these strategies, Uzbekistan can improve environmental sustainability, support economic growth, and contribute to global efforts to achieve SDG 12.